Polarimetric channel characterization of foliage for performance assessment of GPS receivers under tree canopies - Il-Suek Koh; Sarabandi, K. (IEEE transactions on antennas and propagation, 2002)
The attenuation, depolarization, and fluctuation of a microwave signal going through a tree canopy are investigated by developing a Monte Carlo based coherent scattering model. In particular, the model is used to analyze the performance of Global Positioning System (GPS) receivers under tree canopies. Also the frequency and time-domain channel characteristics of a forest are investigated when a transmitter is outside and a receiver is inside a forest. A fractal algorithm (Lindenmayer system) is used to generate the structure of coniferous or deciduous trees whose basic building blocks are arbitrarily oriented finite cylinders, thin dielectric needles, and thin dielectric disks. Attenuation and phase change of the mean field through foliage is accounted for using Foldy's approximation. Scattering of the mean field from individual tree components and their images in the underlying ground plane are computed analytically and added coherently. Since tree trunks and some branches are large compared to the wavelength and may be in the close proximity of the receiver, a closed-form and uniform expression for the scattered near-field from dielectric cylinders is also developed. Monte Carlo simulation of field calculation is applied to a cluster of trees in order to estimate the statistics of the channel parameters, such as the probability density function (pdf) of the polarization state of the transmitted field, path loss, and the incoherent scattered power (the second moment of the scattered field), as a function of the observation point above the ground.